2019
DOI: 10.3390/su11205546
|View full text |Cite
|
Sign up to set email alerts
|

New Building Cladding System Using Independent Tilted BIPV Panels with Battery Storage Capability

Abstract: In order to meet renewable energy goals in the near future, the deployment of photovoltaic (PV) panels on buildings will dramatically increase. The objective of this paper is to introduce an improved design for PV cladding systems that will greatly contribute to meeting these renewable energy goals. Typically, building-integrated photovoltaic (BIPV) panels are vertically oriented as cladding and they are not coupled with individual storage batteries. The proposed cladding couples a tilted BIPV panel with one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Kim et al [29] created a well-developed design of PV cladding systems that will make a significant contribution to meeting the targets for renewable energy and zero-energy building. Normally, photovoltaic panels built into buildings are vertically oriented with no batteries attached [29].…”
Section: Technologies Of Building Integrated Photovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [29] created a well-developed design of PV cladding systems that will make a significant contribution to meeting the targets for renewable energy and zero-energy building. Normally, photovoltaic panels built into buildings are vertically oriented with no batteries attached [29].…”
Section: Technologies Of Building Integrated Photovoltaicsmentioning
confidence: 99%
“…Kim et al [29] created a well-developed design of PV cladding systems that will make a significant contribution to meeting the targets for renewable energy and zero-energy building. Normally, photovoltaic panels built into buildings are vertically oriented with no batteries attached [29]. However, this study proposed a BIPV system for each location that is linked to one or more storage batteries, making the system independent of the other generation of power in the building and referred to as the "Perma-Power Connection Building" cladding feature (Figure 5).…”
Section: Technologies Of Building Integrated Photovoltaicsmentioning
confidence: 99%
“…Unfortunately, increasing the robustness of this legacy system through hardening has limited effects (Alexander‐Bloch, 2012). More recently, it has been found that greater robustness through increased redundancy is possible through permanent continuous onsite power generation coupled with multiple small storage batteries (Kim, Reed, Choe, Wang, & Recart, 2019; Wang, Kim, & Reed, 2016). While complete independent power sourcing generation onsite is not possible yet for most buildings, the capability of rooftop photovoltaic (PV) and BIPV coupled with multiple independent battery systems is possible to increase energy resiliency to buildings.…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…In this manner, the onsite electric power system would be designed to provide the highest level of HVAC services possible to meet the occupant needs. Our ongoing work with BIPV panels coupled with small storage batteries provides a strategy (Kim et al., 2019). In order to generate and store enough power to meet the minimal occupant needs, multiple panels across the building will need to be employed.…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…Monteleone et al proposed an adaptive envelope component, namely SLICE (Solar Lightweight Intelligent Component for Envelopes), equipped with high-efficiency photovoltaic cells, and which is a lightweight and stand-alone component for dynamic envelopes [24]. Double-wedge BPPL (Building Perma-Power Link) panels were proposed and analysed in the case of a mid-rise building in Seattle, Washington [25]. Each cladding panel was designed as a stand-alone system, which will be useful for installation, operation, and maintenance.…”
Section: Introductionmentioning
confidence: 99%